The Influence Of Information Privacy Awareness On Privacy Protection Behavior In Facebook - Fahrezi, Sulthan Muhammad; Candiwan, Candiwan (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
The use of the internet has become very common in today society. Based on a survey by dataindonesia.id, 68.9 percent of the 370.1 million internet users in Indonesia are social media users, and Facebook is one of the most widely used social media platforms in Indonesia, with the number of users growing to 202.2 million by July 2022. Due to this increase and the huge number of users, as well as the amount of personal information stored in it, this can be a vulnerability for Cybercriminals to exploit such as phising or scams. This research was conducted to analyze and determine what factors affect users information privacy concerns towards privacy protection behavior on Facebook. The data were collected by distributing a questionnaire to a total of 417 Facebook users in Indonesia. This research model consists of seven constructs. The research model constructs consist of User's Information Privacy Concerns, Perceived Severity, Perceived Vulnerability, Self-Efficacy, Response Efficacy, Rewards, and Privacy Protection Behavior. This research was analyzed using quantitative methods by processing data through SPSS and AMOS software. The data is processed using the SEM model, which is validated with a confirmatory factor analysis test, a structural model test, and a hypothesis test. The results of this study indicate a positive correlation between User's Information Privacy Concerns and Perceived vulnerability in Privacy Protection behavior, it can be concluded that User's Information Privacy Concerns (UIPC) can affect Privacy Protection behavior (PPB) among Facebook users. Therefore, Facebook users are advised to be more concerned about their privacy information protection behaviors by avoiding any behavior that may put them at risk of privacy threats. This paper suggest users to take measures to prevent any threats to their privacy.